АРҚА БАТЫС ҚЫЗЫЛҚУМНЫҢ БЕЛТАЎ БИЙИКЛИГИНДЕ КЕМИРИЎШИЛЕРДИҢ БИОТОПЛАРДА ТАРҚАЛЫЎЫ - Палуанова, Г.Ж.; Қурбаниязов, А.С.; Алланиязов, Н.П. (FAN va JAMIYAT, 2025)
The article discusses the Beltau Heights, which were divided into four biotopes there were studied where rodent species, their ecological adaptations, and distribution patterns. The studies showed that the main biotopes (lakes around the Akchadarya Canal and coastal sands) in this area demonstrate rodent adaptation to these ecotopes.